DIVERSIFICATION OF PINEAPPLE WASTE THROUGH ECO-ENZYME DOING TRAINING AT THE “QUEEN” PINEAPPLE FARMER GROUP KEDIRI - Tri Ana Mulyati; Fery Eko Pujiono; Umul Farida (International Journal of Engagement and Empowerment, 2023)
Kediri is the largest honey pineapple-producing area in East Java, so it has pineapple farmer groups. The honey pineapple farmer group called "Queens" is one of the pineapple farmer groups in Kediri that creates processed pineapple products such as fresh pineapple fruit, peeled pineapple, and pineapple drink. However, the group is facing an issue of pineapple skin waste that has yet to be utilized. Therefore, expanding pineapple products by using fruit and pineapple skin waste is crucial. One way to do this is by making eco-enzymes. The method used in this activity is a group-based activity method, carried out jointly between the activity team and the pineapple queens farmer group, starting from the planning, implementation, and mentoring to the monitoring and evaluation stages. Community service activities for the "Queens" pineapple farmer group have succeeded in making eco-enzymes from pineapple skin waste. Based on the results of the activity, this activity was able to increase the knowledge of the "Queens" pineapple farmer group, where 100% of the partners already knew the benefits of eco-enzymes and knew the tools and materials, and procedures used in making eco-enzymes from pineapple peels. This activity was also able to improve the skills of the partners of the "Queens" pineapple farmer group, where partners were able to make eco-enzymes from pineapple peel waste very well, starting from preparing tools and materials, mixing ingredients, to packaging eco-enzymes